Public-Private Partnership as Tool for Developing Regional Labor Potential - Kruhlov, V.V.; Tereshchenko, D.A. (Science and Innovation, 2024)
Introduction. The modern direction of infrastructure development is the attraction of the private owner by the state under public-private partnership (PPP) agreements. Problem Statement. Analysis of the possibilities of PPP for the development of labor potential in the modern labor market, taking into account the peculiarities of interaction between public and private capital and on the basis of their economic and social objectives, is an important issue of our time. Purpose. Justification of the objectives and directions of public-private partnership as a tool for the development of labor potential, taking into account the main objectives of the implementation of infrastructure projects. Materials and Methods. Method of theoretical generalization and systematization (to determine the specific features of forming PPP and labor potential in the modern labor market); monographs (a review of scientific ideas about the problem of developing PPP, and the sphere of education); statistical method (to present the key figures that characterize PPP and labor potential); the analytical method (to identify factors that influence implementation of PPP projects as a tool for labor potential development). Results. The implementation of PPP projects has been found to stimulate the labor market and to enhance labor capacity. In case of successful implementation of PPP projects, social problems will be solved due to improved quality of services in the field of education, healthcare, culture, etc. Implementation of the innovation projects of public-private partnership in education and science shapes actually the prerequisites for an increase in figures that characterize labor potential as a whole, and involves staff in specific projects where the key approach is satisfaction of the need for highly qualified specialists. Conclusions. The state policies of PPP development, innovational development of the economy and strengthening labor potential should be aimed at establishing a legislative basis for the institutional environment; introduction of effective economic mechanisms; establishing up-to-date standards which apply to the key development paths of knowledge-based economy.